American visceral Leishmaniasis: a case report - Langoni, H. [UNESP]; Lucheis, S. B. [UNESP]; Da Silva, R. C. [UNESP]; Castro, A. P. B. [UNESP]; Paes, A. C. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos, 2005)
Visceral leishmaniasis is a zoonotic disease caused by parasites of the Leishmania genus. Dog is the major source of infection to man, especially in urban areas. The authors report a case of visceral leishmaniasis in a pit bull female dog from Bocaina, São Paulo, Brazil. The animal presented clinical signs compatible with leishmaniasis, including skin lesions in the body and partial damage of the external ears. The indirect fluorescent antibody test (IFAT) demonstrated a titer of 1280, and promastigote forms of Leishmania sp were isolated by the culture of bone marrow puncture. Cytological analysis of the lymph node and smear of the bone marrow puncture revealed macrophages containing amastigote forms of Leishmania sp in their inner region. The test of Polymerase Chain Reaction (PCR) utilized the primers LINR4 and LIN19, which amplify 720 base pairs, specific for Leishmania sp. The authors discuss the importance of techniques for a quick and precise diagnosis to this serious zoonosis with great impact in animal and public health.
Keywords: Leishmania; zoonosis; dog; diagnosis; hemoculture; serology; polymerase chain reaction (PCR)